Copper dependence of the biotin switch assay: modified assay for measuring cellular and blood nitrosated proteins - Wang, Xunde (2008)
Studies have shown that modification of critical cysteine residues in proteins leads to the regulation of protein function. These modifications include disulfide bond formation, glutathionylation, sulfenic and sulfinic acid formation, and S-nitrosation. The biotin switch assay was developed to specifically detect protein S-nitrosation. In this assay, proteins are denatured with SDS in the presence of methyl methanethiosulfonate (MMTS) to block free thiols. After acetone precipitation or Sephadex G25 separation to remove excess MMTS, HPDP-biotin and 1 mM ascorbate are added to reduce the S-nitrosothiol bonds and label the reduced thiols with biotin. The proteins are then separated on a non-reducing SDS PAGE and detected using either streptavidin-HRP or anti-biotin HRP conjugate. Our examination of this labeling scheme has revealed that the extent of labeling depends on the buffer composition and importantly, on the choice of metal ion chelator (DTPA vs. EDTA). Unexpectedly, using purified S-nitrosated albumin, we have found that “contaminating” copper is required for the ascorbate-dependent degradation of S-nitrosothiol; this is consistent with the fact that ascorbate itself does not rapidly reduce S-nitrosothiols. Removal of copper from buffers by DTPA and other copper chelators preserves approximately 90% of the S-nitrosothiol, while the inclusion of copper and ascorbate completely eliminates the S-nitrosothiol in the preparation and increases the specific biotin labeling. These biotin switch experiments were confirmed using triiodide-based and copper-based reductive chemiluminescence. Additional modifications of the assay using NEM (N-ethylmaleimide) for thiol blockade, ferricyanide pretreatment to stabilize S-nitrosated hemoglobin, and cyanine dye labeling instead of biotin, are presented for the measurement of cellular and blood S-nitrosothiols. These results indicate that degradation of S-nitrosothiol in the standard biotin switch assay is metal ion-dependent and that experimental variability in S-nitrosothiol yields using this assay occurs secondary to the inclusion of metal ion chelators in reagents and variable metal ion contamination of buffers and labware. The addition of copper to ascorbate allows for a simple assay modification that dramatically increases sensitivity while maintaining specificity.